Epidemiologic Investigation of Intestinal Parasite Infection and Associated Risk Factors among Primary Schoolchildren in the Manzini and Lubombo Provinces, the Kingdom of Eswatini - Ai-Wen Yin; Yueh-Lun Lee; Sindisiwe Dlamini; Gugu Maphalala; Chien-Wei Liao; Chia-Kwung Fan (Journal of Tropical Medicine)
Although the deworming program has been executed since 2000, the intestinal parasitic infection (IPI) rates among primary schoolchildren (PSC) in the two provinces of the Kingdom of Eswatini investigated in 2010 remained high, reaching 32.2%. In this study, we monitored the IPI status along with the associated risk factors for PSC in two provinces—Manzini and Lubombo. After consent from their parents/guardians, a total of 316 samples collected from PSC with grades 1 to 3 from four primary schools in Manzini and Lubombo were examined by the Merthiolate-Iodine-Formaldehyde (MIF) method. In addition, demographic characteristics and risk factors acquired by questionnaire surveys were included to be statistically analyzed. The overall prevalence was 40.5% (128/316), of which the infection rate in Manzini and Lubombo was 28.8% (19/66) and 58.3% (74/140), respectively. Pathogenic protozoa had the highest infection rate of 20.6% (65/316), including Entamoeba histolytica/dispar (8.5%, 27/316), Giardia duodenalis (14.6%, 46/316), and Blastocystis hominis (9.8%, 31/316). In terms of helminth infection, the infection rate was quite low, 1.6% only, and these five infected cases included four cases of Hymenolepis nana and one case of Enterobius vermicularis infection. Present study showed that 27.8% (88/316) of PSC were infected by more than one pathogenic parasite. Personal hygiene like washing hands before a meal has a significant protection effect (OR = 0.32, 95% CI = 0.14–0.75, p=0.009). Rain or well water and the type of water supply from which they drank also showed a considerable risk factor (OR = 2.44, 95% CI = 1.25–4.79, p=0.04). The IPI rate in PSC seems unlikely changed compared to that of the previous survey conducted in 2010, especially when the pathogenic protozoan infection rate remains high. Treatment of infected PSC with appropriate medication to reduce intestinal pathogenic protozoan infection should be seriously considered by Eswatini Health Authority.